Psychological and Pedagogical Foundation of Work with Problem Solving Situations as a Means of Forming Universal Educational Activities among Elementary School Children - Iakovleva, Elena N. (International Journal of Psychosocial Rehabilitation, 2020)
The Federal State Educational Standard (FSES) of elementary general education states one of the most important goals of elementary education to be the development of the pupil’s personality on the basis of acquiring universal educational activities which ensure the mastering of the key competences that make up the core of the ability to learn. The topicality of the study is stipulated by the need to develop and apply individual techniques and methods of the formation of universal educational activities among elementary schoolchildren. Therefore, this article is aimed at identifying the possibility of using various methods of handling problem solving situations in order to develop universal learning activities. The article presents basic methods of working with problem solving situations: mastering the way pupils acquire new knowledge; the technique of predicting; verbalization of the sign- graphic model; the model structuring based on the verbal description, creative interpretation and transformation of the model from one type to another; drawing up a chain of reasoning on the selection of the initial data, filling in the gaps in the task, etc. The article can be valuable for the pedagogical theory and practice since the authors have described the experience of working with problem solving situations as one of the means of forming universal learning activities. The materials of the article can be useful in the educational practice of the elementary school in the process of formation of universal educational activities among elementary school childrena.